Investigation on gel polymer electrolyte-based dye-sensitized solar cells using carbon nanotube - Sakali, Somia Mohammed; Khanmirzaei, M.H.; Lu, S.C.; Ramesh, Subramaniam; Ramesh, Kasi (Springer Verlag (Germany), 2019)
A new poly (acrylonitrile) (PAN)-based gel polymer electrolyte (GPE) is fabricated to study the effect of carbon nanotube (CNT) on dye-sensitized solar cell (DSSC) efficiency. The GPEs are examined using electrochemical impedance spectroscopy (EIS) to analyze ionic conductivity. A maximum of 4.45 mS cm −1 ionic conductivity is achieved at room temperature with incorporation of 11 wt.% CNT. Performance of DSSC is examined with a solar simulator, and the highest energy conversion efficiency of 8.87% is achieved with the addition of 11 wt.% CNT. All GPE samples are found to follow Arrhenius model with temperature-dependent ionic conductivity testing. Structural properties are also characterized by X-ray diffraction (XRD) and Fourier-transform infrared (FTIR) spectroscopy. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.